Neuromediators Implicated in Orthodontic Treatment: A Review - Ghazaryan, Eleonora R.; Vardanyan, Gayane S.; Aghajanov, Michail I.; Ter-Poghosyan, Hrant Y.; Nalbandyan, Mikayel S. (Recent Updates in Disease and Health Research Vol. 3, 2024)
Millions of people around the world undergo orthodontic treatment to treat craniofacial disorders, correct their bites, and ultimately achieve a beautiful smile. However, orthodontic treatment has many significant challenges that require a better understanding of the molecular-biochemical mechanisms involved in orthodontic tooth movement. Orthodontic treatment is a multifactorial process, occurring with the participation of many signaling molecules and the involvement of different metabolic pathways. Orthodontic treatment is the finely regulated, continuous process of bone remodeling, which occurs through the highly coordinated interaction of different types of bone cells: osteoblasts, which participate in bone formation, and osteoclasts, which destroy bone. The true picture of the processes mentioned remains to be investigated, but more and more information suggests the possible role of individual neurochemical players in the above-mentioned processes. This review aims to summarize the available data regarding the various neurochemical regulators and receptor systems involved in orthodontic treatment processes.